Fatal and Nonfatal Injury Patterns of Stranded Motorists. Issue 3 (July 2021) - Drake, Stacy A.; Yang, Yijiong; Gao, Si; Mora, Stephen; Garza, Robin; Moore, Laura; Todd, S. Rob; Wilson, Chad; Wolf, Dwayne A.
Abstract : ABSTRACT: Because nonfatal and fatal incidents for stranded motorists are not separated from vehicular accidents, little data are available on incident characteristics. To close this gap, data fields were inserted into databases at a medical examiner's office and two trauma centers to collect injury-related information. Forensic nurses and pathologists aided in forming a collaboration among the agencies involved and supported data collection efforts. Data collected over a 5-year period were examined for injury patterns to determine risk factors affecting these patterns. Of the total sample ( N = 219), 24.7% had spinal injuries resulting in fatal injuries for 46 of 54 individuals. The odds were stranded motorists with spine-related injuries (C1–C7) had 9.13 times higher risk for a fatal outcome compared with those without spine-related injuries. Severe injuries (Abbreviated Injury Scale scores ≥ 4) noted for head/neck (29.7%) and chest (24.2%) were significantly associated with fatality. Of the 219 cases, 22.8% were inside of a stopped vehicle, and 77.2% were outside a vehicle at the time of injury. Outcomes illustrated the success of the interprofessional collaboration between trauma centers and a medicolegal death investigation agency that resulted in data useful for forensic nurses and pathologists documenting evidence, emergency and trauma responding personnel in patient priority stabilization, and injury prevention specialists for highway safety programs.